PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Indrayani, Sry; Munjiatun, Munjiatun; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the students achievment of social studies SDN 023 Sedinginan still low with an average value of 55,25 and minimum completenness criteria (KKM) social studies is 70. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40 %. This research is Classroom action Research (CAR), wich aims to improve the student achievement of social studies class V at SDN 023 Sedinginan with implementation cooperative learning model type Numbered Heads Together (NHT). Formulation of the problem : is the implementation of cooperative learning model type Numbered Heads Together (NHT) can improve students achievment of social studies at SDN 023 Sedinginan. The research was conducted on march 17, 2015 to april 21, 2015 by 2 cyclees. Subjects were students of SDN 023 Sedinginan, totalling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score sycle with the average being, 55,25 In the first cycle improve an average of 65 with increase big as 17,6% and an impove in the second with an average of 95 with increase big as 47,96 %. Activities of the teacher in the learning process in cycle of 58,3 % and the second meeting improve to 70,8 %. cycle II firs meeting and the second meeting improve 83,3 % and the second meeting improve to 95,8%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 54,2 % and a second meeting improve to 62,5% and a second meeting improve to 79,2 %. At the firs meeting of the second cycle with an avarage of 91,7 %. Result in the class V at SDN 023 Sedinginan that the implementation of cooperative learning model Numbered Heads Together (NHT) can improve students achievement of social Studies at fave graderes SDN 023 Sedinginan.Key Words : Model Learning Numbered Heads Together (NHT) Fave graderes students Achievement.